Long-distance propagation of short-wavelength spin waves - Chuanpu Liu (Nature Portfolio, 2018)
Short-wavelength spin waves with high group velocity are one of the key ingredients for the spin-wave based memory-logics. Here the authors demonstrate the propagation of spin waves with wavelength down to 50 nm and group velocity up to 2600 m s−1 using ferromagnetic nanowires grown on a thin Y3Fe5O12 film strip structure.